Human Mesenchymal Stem Cell-Derived Exosomal microRNA-143 Promotes Apoptosis and Suppresses Cell Growth in Pancreatic Cancer via Target Gene Regulation - Wang, Bingyi; Xu, Yan; Wei, Yuhua; Lv, Lixin; Liu, Nanbin; Lin, Rui; Wang, Xiuyan; Shi, Baomin (Frontiers in Genetics, 2021)
Background: This study was to explore the regulatory mechanism of hsa-miR-143-3p and lncRNA RP11-363N22.3—functioning upstream of KRAS—in exosomes derived from human mesenchymal stem cells (hMSCs) in pancreatic cancer. Methods: Western blotting and quantitative PCR were used to determine genes expression. In vitro, cell proliferation, apoptosis, cell cycle and invasion were evaluated using CCK-8 assay, flow cytometry and transwell assays, respectively. In vivo, the effect of hsa-miR143-3p was investigated by tumorigenesis test in nude mice. The association between hsa-miR-143-3p and lncRNA RP11-363N22.3 was investigated using the dual-luciferase assay. Results: hsa-miR-143-3p expression significantly increased in hMSC exosomes than that in human pancreatic cancer cell line (CFPAC-1) exosomes. In vitro, compared to MOCK (CFPAC-1 only) group, cell proliferation and invasion were inhibited and apoptosis was induced in the inhibitor NC (CFPAC-1+MSC-hsa-miR-3p inhibitor NC) group, while these changes were reversed in inhibitor (CFPAC-1+MSC-hsa-miR-3p inhibitor) group. The expression of lncRNA RP11-363N22.3 and genes related to miR-143 significantly decreased in inhibitor NC group compared to MOCK group, and increased in inhibitor group compared to inhibitor NC group. A targeted combinatorial effect was observed between lncRNA RP11-363N22.3 and hsa-miR-143-3p. In vivo, the tumor volume of the mimics (CFPAC-1+MSC-hsa-miR-143-3p mimics) group was smaller than that of mimics NC (CFPAC-1+MSC-hsa-miR-143-3p mimics NC) and MOCK groups. H&E staining showed that there were no obvious pathological changes in MOCK and mimics NC groups, while cell necrosis was seen in some regions in mimics group. Conclusion: hsa-miR-143-3p may promote apoptosis and suppress cell growth and invasion in pancreatic cancer.